Single-Payer Health Care Reform: Cost Considerations in Maine - Bryant, Daniel (Maine Policy Review, 2024)
One of the suggested reforms of our troubled health care system is the publicly funded universal health care, or single-payer, model; one of the arguments against it is its presumed cost. Using 2020 data for Maine (the most complete recent data available), I distinguish and examine three types of health care cost, which are easily confused: the cost of providers’ health care services, the cost the multiple payers pay for those services, and the cost to Maine residents of funding those multiple payers through taxes, premiums, etc. I then estimate what the cost of a single-payer plan to Maine residents would have been in 2020, suggest how a health care income tax could have paid for it, and conclude with the suggestion that single-payer advocates will have to educate the public and the Legislature about cost considerations like these if they expect to win either over to their side.